AB1052 Biosimilars Use in Rheumatology - the Patient Perspective. (10th June 2014) - Berghea, F.; Popescu, C.; Ionescu, R.; Damjanov, N.; Singh, G.
Abstract : Background: Biosimilars are near exact copies of biological drugs that demonstrate similar pharmacokinetics, efficacy and safety profile as the originals. Following the positive regulatory decisions, these molecules have been made available in a number of European countries offering a less expensive alternative to the originals and the subsequent promise of a higher number of treated patients. The novelty of the concept of "near exact copies" creates a large room for debates both in medical community and in rheumatic patient's worlds regarding the right patient for biosimilars. Apart from medical, economical and administrative reasons little is known about the opinion of the most important piece in this complicated puzzle: the rheumatic patient. Objectives: To assess the knowledge, perceptions and attitudes vis-à-vis the biosimilars in potential users of these drugs: rheumatic patients with and without biological therapy. Methods: Rheumatic patients receiving or being on the waiting list for biological therapy were invited to participate in focus group sessions. The discussion scenario covered the following areas: knowledge and acceptance of drug copies; knowledge, perceptions and acceptance of biologics/biosimilars; perception of socioeconomic issues related to these. Two reviewers independently identified trends and relations in the participants' statements; each statement was marked as major when majority of the participants expressed convergent opinions and minor in case just a minority did so Results: 14 rheumatic patients have been involved; 7 of them being on biological therapy. The following statements have been identified as major ones: – Original drugs are better than copies no matter we speak about small molecule or biologic drugs. – A higher price means a better quality. – The characteristics of a drug are highly dependent of the excipients and the quality of production facilities. – There is no difference between originals and biosimilars regarding the standards regulatory agencies used to evaluate them. – When a copy of a drug become available the price of the original decreases. – Once you started with a drug you should have the right to stay on it no matter your doctor certify similar efficacy and safety profile. – Patients on the waiting list have no preference for an original or a biosimilars as long as they intend to trust their doctor's option. – When the co-payment for the original is higher than for biosimmiar the switch becomes acceptable. If a biosimilar is used in western European countries then one should trust it no matter is produced by an unknown company. This is not the case for a biosimilar used in non-European countries. Conclusions: In few areas (but not everywhere) the patient's knowledge about drug (copies) might be deeper than we expect; the socio-economic advantages of biosimilars seems to be fully understood; treating physician should made the choice and assume the responsibilities; in the absence of financial constrictions the idea of a free switch between originals an biosimilars doesn't seem to have many adepts. The study reveals a great need for education and debate in this area in order to fully accommodate the concept of biosimilars in rheumatic patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3531